Multidrug Resistance Protein Transporter and Ins(1,4,5)P3-Sensitive Ca2+-Signaling Involved in Adenosine Triphosphate Export via Gq Protein-Coupled NK2-Receptor Stimulation With Neurokinin A - Jing Sun; Sadaharu Usune; Yumei Zhao; Keisuke Migita; Takeshi Katsuragi (Elsevier, 2010)
The purpose of this study is to identify the membrane transport machinery and cell signaling involved in the neurokinin A-inducible release of adenosine triphosphate (ATP) as an autocrine/paracrine signal from cultured guinea-pig taenia coli (T. coli) smooth muscle cells (SMCs). ATP release evoked by neurokinin A was inhibited by L-659877, a NK2-receptor antagonist; by modulators for Ins(1,4,5)P3-sensitive Ca2+-signaling, U-73122, thapsigargin, and 2-APB; and by W-7, a calmodulin inhibitor, and staurosporine, a protein kinase C (PKC) inhibitor, but not by wortmannin, a phosphoinositide 3-kinase inhibitor. The evoked release was suppressed by a multidrug resistance protein (MRP)-transporter inhibitors, MK-571, indomethacin, and benzbromarone, but not by CFTR-inh 172, a CFTR-Cl− channel blocker, and α-glycyrrhetinic acid, a gap junction hemichannel blocker. Neurokinin A caused a marked accumulation of Ins(1,4,5)P3 and an increase in [Ca2+]i in the cultured cells. These findings suggest that stimulation of Gq/11 protein- coupled NK2 receptor with neurokinin A caused a substantial release of ATP from cultured T. coli SMCs and that the evoked release may be mediated by Ins(1,4,5)P3-sensitive Ca2+-signaling, further by PKC and Ca2+/calmodulin signals, and finally by an activation of MRP transporters as the membrane device. Keywords:: neurokinin A, Gq protein-coupled NK2 receptor, adenosine triphosphate (ATP) release, Ins(1,4,5)P3-sensitive Ca2+-signaling, multidrug resistance protein (MRP) transporter